Short-term Clinical and Microbiological Performance of Resin-modified Glass Ionomer Cement Containing Chlorhexidine for Atraumatic Restorative Treatment - da Silva, Márjully ER [UNESP]; de Sena, Marina D. [UNESP]; Colombo, Natália H. [UNESP]; Pereira, Jesse A. [UNESP]; Chrisostomo, Daniela A. [UNESP]; de Aguiar, Sandra MHCÁ [UNESP]; Cunha, Robson F. [UNESP]; Duque, Cristiane [UNESP] (Jaypee Brothers Medical Publishing, 2023)
Aim: This study evaluated the short-term clinical and microbiological performance of resin-modified glass ionomer cement (RM-GIC) cement containing chlorhexidine (CHX) for atraumatic restorative treatment (ART) in primary teeth. Materials and methods: The clinical trial was conducted in 36 children that received ART in primary molars either with GIC (group I, n = 18) or GIC containing 1.25% CHX (group II, n = 18). The survival rate of restorations was checked 7 days, 3, and 6 months after their application when saliva and biofilm were collected for microbiological assessment of mutans streptococci (MS) counts. Data were analyzed using the Kruskal–Wallis/ Mann–Whitney U tests for clinical analysis and microbiological evaluations (p < 0.05). Results: The survival rate of restorations was similar comparing groups I with II. Microbiological analysis showed a significant reduction in MS levels 7 days after the treatment in both saliva and biofilm of children treated with RM-GIC containing CHX (group II); however, MS counts at 3 and 6 months did not differ from the initial counts. Conclusion: A total of 1.25% CHX improved the microbiological properties of GIC in the short term without impairing the clinical performance of ART restorations. Clinical significance: Glass ionomer cement (GIC) containing CHX could be an alternative in ART procedures with the objective of promoting an additional antimicrobial effect, which is interesting for children with high counts of MS during the initial phase of adaptation to dental treatment.
Keywords: Chlorhexidine; Dental atraumatic restorative treatment; Dental caries; Resin-modified glass ionomer cement